(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article the issues regarding of the Ararat Marz rural population and settlements forming, dynamics (1831–2015) and the modern situations have been discussed. A special significance has been given to the changes in the rural resettlement structure of the province by the settlements population size, the distribution of population and settlements above sea level, as well as by the production specialization and socioeconomic development problems of the rural settlements.